2018
DOI: 10.1186/s12610-018-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Curative GnRHa treatment has an unexpected repressive effect on Sertoli cell specific genes

Abstract: BackgroundFollicle stimulating hormone and testosterone stimulate Sertoli cells to support germ cell function and differentiation. During mini-puberty, when gonadotropin (GnRH) stimulates increases in plasma luteinizing hormone (LH) and testosterone levels, gonocytes are transformed into Ad spermatogonia. In cryptorchidism, impaired gonadotropin secretion during mini-puberty results in insufficient LH and testosterone secretion, impaired gonocyte transition to Ad spermatogonia, and perturbed Sertoli cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 84 publications
2
7
0
Order By: Relevance
“…Of interest, 4 genes localized in the male-specific Y region, RBMY1B , RB-MY1E , RBMY1J , and TSPY4 , show reduced mRNA levels in HIR samples and also positively responded to GnRHa treatment. This observation supports data of global conservations of the epigenetic pattern associated with the sequences of the same origin (X-transposed, X-degenerate, and ampliconic) [Gegenschatz-Schmid et al, 2018]. …”
Section: Germ and Sertoli Cell Gene Stimulation By Gnrh Treatmentsupporting
confidence: 77%
“…Of interest, 4 genes localized in the male-specific Y region, RBMY1B , RB-MY1E , RBMY1J , and TSPY4 , show reduced mRNA levels in HIR samples and also positively responded to GnRHa treatment. This observation supports data of global conservations of the epigenetic pattern associated with the sequences of the same origin (X-transposed, X-degenerate, and ampliconic) [Gegenschatz-Schmid et al, 2018]. …”
Section: Germ and Sertoli Cell Gene Stimulation By Gnrh Treatmentsupporting
confidence: 77%
“…Intriguingly, a study reported that the early postnatal rise of inhibin B at 3 months of age was positively correlated with LH and testosterone and was negatively correlated with FSH [Main et al, 2006]. There has been raised the possibility that Sertoli cell proliferation during mini-puberty depends more on LH and secondary testosterone than on FSH [Gegenschatz-Schmid et al, 2018]. From mid-puberty and onwards in adulthood, inhibin B correlates negatively with FSH [Crofton et al, 2002].…”
Section: Discussionmentioning
confidence: 97%
“…To emphasize if inhibin B is a promising tool in the evaluation of fertility, this correlation indeed needs more research. The transformation of gonocytes into Ad spermatogonia has been suggested to be initiated by elevated FSH, LH, and testosterone, as gonadotropinreleasing hormone (GnRH) stimulation before and after orchiopexy in cryptorchid boys had a higher number of Ad spermatogonia versus those who did not receive stimulation [Gegenschatz-Schmid et al, 2018]. Overall, this implies that the maturation of spermatogonia fails in cryptorchid testes and may result in a loss in the total number of germ cells, indicating that the potential for male fertility may be established in mini-puberty, during a period between 1 and 3 postnatal months, where transformation of gonocytes into Ad spermatogonia takes place.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of gonadotropins is safe, well tolerated and effective. Finally, new evidences suggest also the possibility of treatment with a gonadotropin-releasing hormone agonist, which induces gonocytes to differentiate into Ad spermatogonia and rescues fertility ( 84 ). As regards hypergonadotropic hypogonadism, one of the most frequent causes is Turner syndrome (TS).…”
Section: Minipuberty and Hypogonadismmentioning
confidence: 99%